THE IMPACT OF RADEC MODEL ON PRE-SERVICE ELEMENTARY TEACHERS' UNDERSTANDING OF FRACTIONS AND ITS CORRELATION TO SELF-REGULATED LEARNING - Irawati, Riana; Sopandi, Wahyu; Sujana, Atep (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2024)
The low mathematical comprehension and poor self-regulated learning of pre-service elementary school teachers are behind this research. This study aims to determine the effect of implementing the RADEC model on increasing the conceptual understanding of prospective elementary school teachers on fractions and determine whether there is a correlation between the students' self-regulated learning in answering pre-learning questions and their mathematical comprehension. Quantitative research methods were carried out in this study, with the design of the one-group pretest-postest. The research was conducted at one of the universities in West Java, with research subjects of 88 students from an elementary school teacher education program. Tests and questionnaires are the primary research instruments in this study. The results showed an increase in students' mathematical comprehension after implementing the RADEC model, and there was a low correlation (r = 0.309) between self-regulated learning and mathematics conceptual understanding of fractions among the students